Design And Fabrication Of Water Level Control Valve For Acid Filling System - Cheong, Der Hwa (Universiti Sains Malaysia, 2017)
Acid filling system is one of the important manufacturing process to lead acid battery. The study is to design a system to provide the constant acid flow rate into every division of the battery by using control valve. Other than the constant flow rate, the study also has to provide the filling time of the battery container is less than 30s. The system for the study has been designed. The head loss and volume flow rate of the system are calculated. The flow in the system is simulated by using Ansys simulation and the results show that the design system is able to provide constant flow rate after having some set up time and with the installation of control valve.